Ectopic automaticity induced in ventricular myocytes by transgenic overexpression of HCN2. (March 2015) - Oshita, Kensuke; Itoh, Masayuki; Hirashima, Shingo; Kuwabara, Yoshihiro; Ishihara, Keiko; Kuwahara, Koichiro; Nakao, Kazuwa; Kimura, Takeshi; Nakamura, Kei-ichiro; Ushijima, Kazuo; Takano, Makoto
Abstract: Hyperpolarization-activated cyclic nucleotide-gated channels (HCNs) are expressed in the ventricles of fetal hearts but are normally down-regulated as development progresses. In the hypertrophied heart, however, these channels are re-expressed and generate a hyperpolarization-activated, nonselective cation current ( I h ), which evidence suggests may increase susceptibility to arrhythmia. To test this hypothesis, we generated and analyzed transgenic mice overexpressing HCN2 specifically in their hearts (HCN2-Tg). Under physiological conditions, HCN2-Tg mice exhibited no discernible abnormalities. After the application of isoproterenol (ISO), however, ECG recordings from HCN2-Tg mice showed intermittent atrioventricular dissociation followed by idioventricular rhythm. Consistent with this observation, 0.3 μmol/L ISO-induced spontaneous action potentials (SAPs) in 76% of HCN2-Tg ventricular myocytes. In the remaining 24%, ISO significantly depolarized the resting membrane potential (RMP), and the late repolarization phase of evoked action potentials (APs) was significantly longer than in WT myocytes. Analysis of membrane currents revealed that these differences are attributable to the I h tail current. These findings suggest HCN2 channel activity reduces the repolarization reserve of the ventricular action potential and increases ectopic automaticity under pathological conditions such as excessive β-adrenergic stimulation. Highlights: We generated transgenic mice selectively overexpressing HCN2 in their hearts. β-Adrenergic stimulation induces idioventricular rhythm in HCN2-Tg hearts. β-Adrenergic stimulation reduces repolarization reserve in HCN2-Tg myocytes. β-Adrenergic stimulation induces automaticity in HCN2-Tg myocytes. HCN2 modifies the myocardial phenotype to increase arrhythmogenic potential.